EXPLORING THE SIGNIFICANCE OF INTELLECTUAL LEADERSHIP: PERSPECTIVES OF PROFES SORS IN HIGHER EDUCATION IN KAZAKHSTAN - Kaldar, Symbat (Nazarbayev University Graduate School of Education, 2023)
Currently, the topic of intellectual leadership in higher education is shaping academic discourse. Intellectual leadership includes the ability of academics to influence their fields through intellectual work, mentoring, and innovation. This work aims to clarify the role of intellectual leadership in universities, its importance in the formation of scientific discourse, and the development of scientific innovations. Special attention is paid to explaining how intellectual leadership affects the organizations, the development of teaching staff, and student learning outcomes. The study uses a qualitative research method, including a literature review and information from interviews, for a comprehensive analysis of intellectual leadership in higher education institutions. The study also provides a systematic review of the existing literature, supplemented by empirical data for a comprehensive analysis of intellectual leadership in higher education institutions. This research paper also analyzes in detail how this affects the field of knowledge, forming theoretical ideas about intellectual leadership in higher education institutions. It emphasizes the need for further research to explore new trends, practices, and challenges in developing intellectual leadership among scientists in higher education institutions in an increasingly globalized world
Keywords: Type of access: Restricted; Intellectual leadership; Higher education; academic development; mentoring; academic leadership